Environmental and safety: Sustainable development - Kabbashi, Nassereldeen Ahmed; A. Galal, Fatima (2013)
Great number of verses in Qura’n and multiple sayings of the Prophet Muhammad indicate the great importance that has been given to safety. Qur’an and Sunnah are the certainty that is never mixed with doubt, the light that dissipates darkness and the correct guidance that repels misguidance and prevents loss and failure for all of mankind. Allah (SWT) says: “Verily, this Qur’an guides to that which is most just and right.” (17:9). The concept of safety issue as of sustainable development in Islam can be defined as “absolute safety of mankind in his-self, property, blood and wealth in addition to the balanced and simultaneous realization of consumer welfare, economic efficiency, attainment of social justice, and safe of socially interactive based process”. Based on teaching of Islam, the universe has been created by Allah (God) with a specific purpose and for a limited time to enjoy and survive. The paper will highlight sustainability of safety to mankind in consuming all natural resources – land, water, air, fire (energy), forests, oceans – that considered the right and the joint property of the entire humankind. Since Man is Khalifatullah (the vicegerent of Allah) on earth, he should take all preventive measure to ensure the interests and rights of others, and regard his mastery over his allotted piece of land as a joint ownership with the next generation.